The Iranian diaspora in Malaysia: a socio-economic and political analysis - Mogshed, Ahmed Bani Kamal; Hossain, Ishtiaq (Taylor & Francis Group, 2016)
This paper is a preliminary study on the Iranian diaspora in Malaysia. It explores the composition of the Iranian diaspora in Malaysia, and the push factors that have led to its migration to Malaysia. The paper also sheds light on different types of business operations the Iranians are engaged in Malaysia. Having done this, the paper analyses the socio-economic impacts of Iranians expatriates on their host society. It also examines the Iranian expatriates’response to the political and social developments taking place in Iran. Finally, the paper deals with the Iranian government’s policy towards the Iranian diaspora in Malaysia.